Fear of COVID-19 among employees of large companies and vaccination against COVID-19 - a cross-sectional study (Silesia, Poland) - Grajek, Mateusz; Krupa-Kotara, Karolina; Sobczyk, Karolina (Journal of Education, Health and Sport, 2022)
Introduction and Objective. The COVID-19 pandemic has significantly affected the functioning of the entire globe. By the end of December 2020, the disease had been diagnosed in more than 82 million people worldwide, and nearly 2 million people had died. The main preventive measure was to develop an effective vaccine as soon as possible, which Pfizer/BioNTech, Moderna, AstraZeneca and Gamaleya Center managed to do in late 2020. The first vaccines arrived in Poland after the end of December 2020, but their appearance was not without controversy. The aim of this study was to compare respondents' opinions on COVID-19 vaccination with the results of the assessment of fear of infection. Material and methods. The opinions of 300 employees of large companies on COVID-19 vaccination and fear of SARS-CoV-2 (FCV-19S) infection according to Ahorsu were checked. Results. It was shown that 54% of the respondents express a willingness to vaccinate whenever possible, while 42% are not interested in vaccinating. In favor of the willingness to vaccinate is the option to return to the standard of living before the COVID-19 pandemic - 72%, and the desire to protect those around them from possible infection - 46%. Among opponents of vaccination, the predominant opinion is that the vaccine has not undergone enough testing and is not safe for health - 68%. Discussion. COVID-19 vaccination is one of the major medical successes of recent years and a safe way to prevent SARS-CoV-2 infection. It is worrying that those who opt out of vaccination indicate that they do not have enough information about vaccination (44%), and this is an issue that needs to be changed quickly. Conclusions. Those who express a willingness to vaccinate are more likely to have a higher level of fear of SARS-CoV-2 infection than those who have not expressed a willingness to vaccinate. Nearly half of non-vaccinators indicate that there is too little information about vaccination.